Occurrence and Environmental Risk Assessment of Contaminants of Emerging Concern in Brazilian Surface Waters - Oliveira, Thiessa M. A. (2024)
We investigated the occurrence and the environmental risk of eight contaminants of emerging concern (CECs; acetaminophen, naproxen, diclofenac, methylparaben, 17β-estradiol, sulfathiazole, sulfadimethoxine, and sulfamethazine) in three Brazilian water bodies, namely, the Monjolinho River Basin (São Paulo State), the Mogi Guaçu River (São Paulo State), and the Itapecuru River (Maranhão State) in three sampling campaigns. The CECs were only quantified in surface water samples collected at the Monjolinho River Basin. Acetaminophen, naproxen, and methylparaben were detected in the range of <200 to 575.9 ng L−1, <200 to 224.7 ng L−1, and <200 to 303.6 ng L−1, respectively. The detection frequencies of the three measured compounds were between 33% and 67%. The highest concentrations of CECs were associated with intense urbanization and untreated sewage discharge. Furthermore, CEC concentrations were significantly correlated with total organic carbon, electrical conductivity, and dissolved oxygen levels, suggesting that domestic pollution from urban areas is an important source in the distribution of CECs in the Monjolinho River Basin. The environmental risk assessment indicated a high risk for acetaminophen (risk quotient [RQ] values between 2.1 and 5.8), a medium risk for naproxen (RQs between 0.6 and 0.7), and a low risk for methylparaben (RQs < 0.1) to the freshwater biota of the Monjolinho River Basin. Our findings show potential threats of CECs in Brazilian water bodies, especially in vulnerable areas, and reinforce the need for improvements in environmental regulations to include monitoring and control of these compounds in aquatic systems. Environ Toxicol Chem 2024;43:2199–2210. © 2024 SETAC.